(3GdGMUGA GdJWHjbj (B/s - (3GdfYjej, eMeO YHO GdYGds ((3YeGf(B: s (3OGQ hGFd(B, s, 2007)
(3eaGgje CSGSjI (B-(3ebOeI aj fXQjI GdGMJeGdGJ (B-(3GdeJZjQGJ GdYThGFjI (B-(3GdJhRjYGJ GdGMJeGdjI (B-(3GdGQJHGW hGdGfMOGQ GdNWj GdHSjW (B-(3JMdjd GdJHGjf (B-(3GdGNJHGQGJ GddGeYdejI (B-(3GdSdGSd GdRefjIs
(3HHdjhZQGajG(B: (3U(B. 387-389 (3;GdedGMb U(B.393s
Keywords: (3GdGMJeGdGJs; (3GdGMUGAs; (3GdGMUGA GdJMdjdjs